Room Steering Temperature Determination with Variable Concerned of Driver Conditions Who are Sleep Deprived and Road Condition - Ferdinand, Ryan; Siswanto, Daniel; Susanto, Sani (Jurnal Improsci, 2024)
Among the main reasons for the high death rate worldwide are traffic accidents. The most common cause of road accidents is driver fatigue. Not getting enough sleep is one thing that makes people tired. A study on how sleep-deprived sleep-deprived drivers felt about themselves was conducted, and the results showed that they were tired. A potential preventive measure against the driver's extreme weariness is the room steering temperature. The goal of this research is to find the room temperature range that produces the most minor drowsiness is this research's goal. The research used six treatments in a 40-minute driving simulator: hot, cold, pleasant room temperature steering, and monotonous and non-monotonous road conditions. With the Electroencephalogram, one may measure one's state of sleepiness by monitoring brain wave activity. Six treatments were administered to each of the study's four young adult male participants. Teta, alpha, and beta wave powers are derived by processing data from brain wave activity using Matlab R2009A. An ANOVA test is used to discover which factors affect the degree of drowsiness by using the ratio of sleepiness level, which is determined using the equation (θ + α) /β. ANOVA test results indicated that while road conditions and room steering temperature impacted sleepiness, their interaction had no effect. Just the hot-cold level is found to be significantly different by the Tukey and Newman Keuls tests. For sleep-deprived drivers, the temperature differences between hot and cold conditions result in varying drowsiness. The research's practical conclusion is that, for sleep-deprived drivers, a hot temperature range (>26°C–29°C) can result in the lowest level of tiredness.